Analysis of Attributive Endocentric Phrases on the Online Media Website "Literature Is Officially Entered in the School Curriculum as an Effort to Grow Literacy Capability" - Zulfia Raisya Siregar; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
This research aims to analyze the use of attributive endocentric phrases in the online media opinion “Literature Officially Enters the School Curriculum as an Effort to Grow Literacy Skills” Edition 21 May 2024. This statement contains the pattern and format of attributive endocentric phrases. Contains all important sentences used in the Indonesian online media “ Literature Is Officially Entered In the School Curriculum as an Effort to Grow Literacy Capability” May 21 2024 Edition, is the object of this research. Data collection techniques use library, reading, and note-taking methods. This research reveals that there are many types of phrases, in accordance with this research, namely analyzing attributive endocentric phrases. This research helps develop a syntactic theory of phrases, especially attributive endocentric phrases, and expands our knowledge of attributive endocentric phrases.